Elucidating Unique Sources and Persistent Hydrologic Pathways of Chloride to Perennial Freshwater Streams: Root River Analog in a Cold-Weather Environment - (:unkn) unknown (My University, 2023)
Chloride in freshwater streams is increasing in concentration, persisting throughout the year, and contributing to the salinization of water resources. The primary source and pathway of chloride in cold-weather environments are thought to be road salt and runoff. However, mounting evidence displays that other sources and pathways of chloride play an important role yet studies to elucidate them at a high resolution, both temporally and spatially, and across diverse land use are lacking. In this study, chloride was quantified continuously for an urban and rural stream year-round in a watershed thought to be heavily impacted by road salt. Bivariate mixing diagrams and hydrograph separation showed that road salt and groundwater were the predominant source and pathway of chloride year-round and across the watershed. Soil leaching and chloride budget data showed that soils served as both sources and pathways across the watershed and chloride persisted year-round.
Keywords: Chloride Transport; Hydrograph Separation; Mass Loading; Road Salt; Salinization